2020
DOI: 10.3390/su12208420
|View full text |Cite
|
Sign up to set email alerts
|

Forward Thinking for Sustainable Business Value: A New Method for Impact Valuation

Abstract: How can a company commit to maximizing stakeholder value while maintaining financial performance? Companies increasingly have the ambition to provide stakeholder value to their owners and shareholders, employees, consumers, suppliers, partners, the environment, and future generations. However, such companies often face difficulties in demonstrating the value they bring to stakeholders, due to the lack of universal methods for assessing their impact. Besides the practical need to develop a method for impact val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…There is no information on sustainable consumption. Sustainability indicators provide information on environmental, social and economic policies but cannot compare and contrast these factors (Buchholz, H., et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…There is no information on sustainable consumption. Sustainability indicators provide information on environmental, social and economic policies but cannot compare and contrast these factors (Buchholz, H., et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, using a novel methodology to evaluate the sustainable business value of companies and referring to a case study about the healthcare sector, Ref. [55] show that a firm's sustainable business conduct can positively affect total shareholder returns and hence financial performance. Similarly, Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale or justification for this research question is that there is widespread interest in identifying and overcoming barriers to accounting practice adaptation for CE implementation (Coalition CE, 2022;Circle Economy, 2021World Economic Forum, 2021;KPMG et al, 2019;Barker et al, 2020;Buchholz et al, 2020), as accounting and finance have been identified as a critical enabler and driver of CE transition. Thus exploring this research question will create a relevant forum for proposing actions and initiatives to enhance accounting practices and CE implementation.…”
Section: Introductionmentioning
confidence: 99%